اسلام کے تصورِ قصاص کی اہمیت اور ضوابط :اسلامی تعلیمات اورمغربی فکر کے تناظر میں ایک مطالعہ (Al-Qamar, 2019)
This article discusses the Islamic law of Qiṣāṣ and its rules from the perspectives of Islamic teachings and Western approach. It shows that Qiṣāṣ has been devised for the establishment of peace in human society and for the prevention of crime. Quran calls this law life for the humanity. Islam values ​​human life more than the sanctity of Kaʻba. In Islamic law of Qiṣāṣ the nature of the crime and the punishment should be exactly the same. For example, if someone's finger has been cut off, the same finger of the culprit will be cut off only to the extent from which he cut off the finger. Many none-Muslim intellectuals also have confessed that Qiṣāṣ is the best solution to the growing crime of murder. There is no violation of human rights in this law, as it is commonly propagated by some Western writers.
Keywords: Qiṣāṣ; Islam; Importance; Western Scholars